PMO-248 Mucosal upregulation of arachidonic acid production in active ulcerative colitis: delivery of pro-inflammatory eicosanoid precursors. (28th May 2012) - Pearl, D S; Masoodi, M; Eiden, M; Brummer, J; Gullick, D; Whittaker, M A; Nitch-Smith, H; Brown, J F; Shute, J K; Mills, G; Philip, C C; Trebble, T M
Abstract : Introduction: Ulcerative colitis (UC) is a colonic inflammatory disorder of unconfirmed aetiology. Eicosanoids, inflammatory mediators involved in UC pathogenesis, are enzymatically converted from dietary polyunsaturated fatty acids (PUFA), arachidonic acid (AA) and eicosapentaenoic acid (EPA), themselves competitive substrates also generated via a fatty acid (FA) biosynthetic cascade. Dietary studies using fish oil-derived EPA have been disappointing in UC; we hypothesised that the PUFA biosynthetic pathway in inflamed tissue is altered. This study evaluated PUFA profile in inflamed and non-inflamed mucosa from UC patients and compared to matched controls. Methods: Ethical approval was obtained. Patients were prospectively recruited from outpatients' clinics. Mucosal biopsies at flexible sigmoidoscopy (FS) were taken from UC patients within inflamed and normal proximal mucosa. Age-sex matched control patients undergoing FS for functional symptoms were compared. Inflammation was scored endoscopically and histologically. Membrane bound FA (MBFA): Biopsies were spiked with deuterated internal standard, followed by liquid-liquid extraction and quantitative gas chromatography mass spectrometry (MS). Free Fatty Acid (FFA): Biopsies were homogenised, followed by solid phase extraction and liquid chromatography orbitrap MS. Data were expressed as percentage abundance. Dietary fatty acid analysis was undertaken. Wilcoxon signed rank pair and Spearman's correlation analysis were employed. Results: 69 active UC patients (54 paired normal/inflamed mucosa) and 69 controls were compared. No biologically significant differences were noted between endoscopically normal mucosa from UC patients and controls other than DPA (p<0.0025). Inflamed mucosa compared to non-inflamed mucosa demonstrated highly significant reduction in LA and αLNA (p<0.0001) and increased AA, DPA, and DHA (p<0.0001); EPA was reduced (p<0.005). The ratio of AA/EPA was increased in inflamed mucosa (p<0.0001). These findings are consistent between MBFA and FFA and correlate with severity of inflammation. Conclusion: Mucosal PUFA bioavailability is altered in active UC, with significant elevation of AA and reduction of LA, αLNA and EPA. This suggests modification of the FA biosynthetic pathway with elevated delivery of AA as a precursor of pro-inflammatory eicosanoids in active UC. These findings may explain the lack of efficacy of supplemental fish oil and suggests new alternative therapeutic targets. Competing interests: None declared.